(untitled) (CSIAM Transactions on Applied Mathematics, 2023)
We consider a diffusion and a wave equations ∂^k_tu(x,t) =∆u(x,t)+μ(t)f(x), x∈Ω, t>0, k=1,2 with the zero initial and boundary conditions, where Ω ⊂R^d is a bounded domain. We establish uniqueness and/or stability results for inverse problems of determining μ(t), 0